Tantangan Terbesar dalam Pembangunan Berkelanjutan: Upaya Meningkatkan Kesadaran Lingkungan yang Rendah di Kalangan Masyarakat di Kota DKI Jakarta - Kurniawan, Heikelindra; Umamah, Reza; Zuhrah, Nesya; Mahdalena, Vina (Universitas Islam Balitar, 2024)
Sustainable development is a global goal that faces many challenges, especially in large cities such as the Jakarta metropolitan area in Indonesia. One of the biggest challenges is the low level of public awareness of the environment. This article examines the application of the diffusion of innovation theory introduced by Everett Rogers as an approach to increasing environmental awareness and behavior in the Jakarta metropolitan area. By identifying environmentally friendly innovations, recognizing target groups and implementing appropriate communication strategies, people's behavior must be changed towards a more sustainable lifestyle. This strategy includes personal communication, education and information, demonstration and experimentation. Additionally, support and training, as well as obtaining feedback, are important parts of the adoption and implemetation process. This research concludes thnat the innovation diffusion approach can be an effective solution for increasing environmental awareness in the Jakarta metropolitan area. Implementing this model requires collaboration between government, the private sector, NGOs and the community. It is hoped that the success of these initiatives will not only improve the city's environmental conditions, but also help achieve broader sustainable development goals in Indonesia.